Evaluation of Vitamin B12 Deficiency in Hospitalized Infants: A 5-Year Experience - Türkmenoğlu, Yelda; Uzunhan, Tuğçe Aksu; Türkkan, Emine; Levent, Ayşenur; Bezen, Diğdem; Beşer, Ömer Faruk; Karbuz, Adem (Cerrahpaşa Medical Journal, 2022)
Objective: Vitamin B12 deficiency in children can manifest itself with neurodevelopmental retardation, convulsion, hypotonia, tremor, faltering growth, and anemia. This retrospective study aims to compare the clinical and laboratory findings of infants with severe and non-severe vitamin B12 deficiency. Methods: Children, hospitalized in the infant clinic and administered vitamin B12 therapy between April 2016 and April 2021 were included. A complete blood count, levels of ferritin, vitamin B12, folate, lactate dehydrogenase, and serum homocysteine were measured in all patients. In addition, the laboratory findings of patients with vitamin B12 levels ≤100 pg/mL (severe deficiency) and those with higher levels were compared. Results: The mean age of the 106 children included in the study was 6.8 ± 4.5 (range: 1-20) months, and 66 (62.3%) of them were male. Fifty-one (48.1%) patients showed neurological symptoms, 29 (27.4%) patients had faltering growth, and 45 (42.5%) patients had anemia. The mean levels of serum B12 in patients were 109.28 ± 40.37 pgm/mL, homocysteine was 18.81 ± 13.54 μmol/L, and levels of hemoglobin were 9.94 ± 2.11 g/dL. Vitamin B12 levels were low in 23 (76.6%) of 30 mothers. The mean hemoglobin and hematocrit levels were statistically significantly lower (P = .007; P = .020, respectively), and the mean folate, LDH, and homocysteine levels were statistically significantly higher in severe vitamin B12 deficiency group (P = .047; P = .009; P = .011, respectively). Conclusion: Vitamin B12 deficiency can manifest itself with different symptoms in young children without having anemia. Screening newborns for this deficiency may help prevent these early signs in infants. Cite this article as: Türkmenoğlu Y, Aksu Uzunhan T, Türkkan E, et al. Evaluation of vitamin B12 deficiency in hospitalized infants: A 5-year experience. Cerrahpaşa Med J. 2022;46(2):108-114.